World Development Report 1987 : Barriers to Adjustment and Growth in the World Economy ; Industrialization and Foreign Trade ; World Development Indicators. - World Bank. (New York : : Oxford University Press, 1987)
This report, consisting of two parts, is the tenth in the annual series assessing development issues. Part I reviews recent trends in the world economy and their implications for the future prospects of developing countries. It stresses that better economic performance is possible in both industrial and developing countries, provided the commitment to economic policy reforms is maintained and reinforced. In regard to the external debt issues, the report argues for strengthened cooperation among industrial countries in the sphere of macroeconomic policy to promote smooth adjustment to the imbalances caused by external payments (in developing countries). Part II reviews and evaluates the varied experience with government policies in support of industrialization. Emphasis is placed on policies which affect both the efficiency and sustainability of industrial transformation, especially in the sphere of foreign trade. The report finds that developing countries which followed policies that promoted the integration of their industrial sector into the international economy through trade have fared better than those which insulated themselves from international competition.
Each issue has also a distinctive title.
Includes bibliographical references.
oif 31/01/2019
Ref.
Keywords: Economic development; Nature and nurture; Adaptation (Biology); Ecology; Euthenics; Social indicators; Economic history; Developing countries